Medición de la calidad y caracterización de las visitas domiciliarias de Cuna Más: Validación del HOVRS-A+2 en Perú y de una corta lista de verificación para su uso a escala - Marta Rubio-Codina; Marta Dormal; M. Caridad Araujo (Inter-American Development Bank (IDB), 2018)
– As home visiting programs continue to expand, it is crucial to develop cost-effective methods to monitor their quality that are feasible at-scale. This paper compares two instruments widely used among home visiting services in the US to a simpler checklist in the context of Peru's Cuna Mas Program. The paper aims to document the structure, content and level of process quality of the Cuna Mas home visits. Its main contribution is to empirically identify a subset of twenty-seven items that focus on critical aspects of quality and that are feasible to collect on a routine-basis as part of program monitoring efforts.
Keywords: I12; J24; O15; 330; home visiting; quality; child development; monitoring; HOVRS; HVCCF; scalability